Hidup Lansia Berkualitas melalui Peran Keluarga Lewat Aktivitas Masyarakat Berbasis Budaya Bali: Penelantaran Lansia - Handi Partiwi, Putu (STIKes Hamzar, 2024)
In 2030, Indonesia is estimated to get a demographic bonus by increasing the number of elderly people. The challenge in the future is how to maintain and even improve the quality of life of the elderly amidst the challenges of the emergence of several degenerative diseases, the aging process, and meeting the needs and independence of the elderly. When viewed from the cases that are currently developing, if not handled properly, it will certainly lead to an increase in cases of elderly neglect or other problems related to elderly health. This study aims to examine the causes of elderly neglect and the role of the family in preventing elderly neglect. The literature review search method uses an online electronic database using the DOAJ (Directory Of Open Access Journal) database (2018-2024) and Google Scholar (2015-2024) using the keywords elderly neglect and family roles, 11 articles were analyzed. It can be concluded that the role of the family in preventing neglect of the elderly as an effort to improve the quality of life of the elderly can be done by collaborating several programs or development methods or models of elderly patient care for family members, health cadres or health workers and assistance to the elderly by the family in community activities based on Balinese culture (Ngayah, Sangkep in Banjar, Seka Gong and Tari, Seka Banten, Seka Mekidung, Seka Subak).